1999
DOI: 10.1359/jbmr.1999.14.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Human NELL-1 Expressed in Unilateral Coronal Synostosis

Abstract: Surgical correction of unilateral coronal synostosis offers a unique opportunity to examine the molecular differences between an abnormal and a normal cranial suture. We isolated and identified a cDNA fragment whose expression was up-regulated in the premature fusing and fused coronal sutures, as compared with normal coronal sutures. The nucleotide sequence of the full-length cDNA of this gene, human NELL-1, has ∼61% homology with the chicken Nel gene. Both chicken Nel and human NELL-1 are comprised of six epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
159
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 153 publications
(165 citation statements)
references
References 36 publications
2
159
0
4
Order By: Relevance
“…6 We have previously identified exencephaly-like characteristics in Nell-1 transgenic embryos. 22,28 Our previous studies have demonstrated the role of NELL-1 in human and murine CS, 22,23,28 while the current studies were performed to further investigate the effects of Nell-1 overexpression on mouse embryonic development and the corresponding molecular mechanism.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…6 We have previously identified exencephaly-like characteristics in Nell-1 transgenic embryos. 22,28 Our previous studies have demonstrated the role of NELL-1 in human and murine CS, 22,23,28 while the current studies were performed to further investigate the effects of Nell-1 overexpression on mouse embryonic development and the corresponding molecular mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…The NELL-1 gene is preferentially expressed in neural crest derived tissues including intramembranous cranial bone and neural tissue. 23 Furthermore, our Nell-1 transgenic mouse model demonstrates craniosynostosis phenotypes of varied degrees and increased apoptosis in osteoblasts. 28 Also, AdNell-1 transduced MC3T3-E1 osteoblasts undergoing apoptosis demonstrate increased Fas expression.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…NEL-like molecule-1 (NELL-1) is an osteoinductive growth factor first identified through its overexpression in pathologically fusing suture specimens from patients with craniosynostosis. 1,2 Transgenic Nell1-overexpressing mice recapitulate craniosynostosis-like phenotypes, exhibiting gross calvarial bone overgrowth and increased osteoblast differentiation. 3 Conversely, Nell1 deficiency severely disrupts bone growth, as mice with nonsense mutations in Nell1 die perinatally with major skeletal anomalies in the craniofacial complex, spine, and long bones.…”
mentioning
confidence: 99%
“…8 NELL-1 can also transiently activate mitogen-activated protein kinase signaling to induce RUNX2 phosphorylation and osteogenic differentiation. 9 Recently, we demonstrated that osteoinductive effects of NELL-1 are partially mediated through binding to the intracellular molecule apoptosis related protein 3 and integrin-b 1 . 10 In translational models of bone repair, exogenous NELL-1 induces potent osseous healing of critical-sized rat calvarial defects, 11 repair of rat femoral segmental defects (FSDs), 12 as well as successful spinal fusion in rats 13,14 and sheep.…”
mentioning
confidence: 99%